INFLUENCE OF PROCESS PARAMETERS ON CELLULASE PRODUCTION BY Trichoderma viride (MTCC 800) EMPLOYING SOLID STATE FERMENTATION - P. R. KAKDE and S. C. AITHAL * (The Journal of Research ANGRAU, 2022)
In this study, the effect of physico-chemical parameters on the production of cellulasefrom Trichoderma viride (MTCC 800) were examined using five different agricultural residuesnamely banana peel, groundnut shell, corn cob, sugarcane bagasse, and pigeonpea stalk. Theprocess parameters examined were pretreatment method, supplementation media, initial mediapH, incubation period, temperature, and leaching agent. Among the parameters studied, maximumcellulase production was obtained on all the substrates treated with 1 N H2SO4 supplemented withMandel’s medium of pH 5.5-6 after 6-8 days of incubation at 30-36°C and 0.05 M phosphatebuffer (pH 7.0) as a leaching agent.